EFL Learners’ Perceptions on ZOOM Application in the Online Classes - Nadila Nuraziza; Lulud Oktaviani; Fatimah Mulya Sari (Univeristas Negeri Gorontalo, 2021)
Pandemic Covid-19 brings impactful aspects for several sectors, especially in the education sector. The teaching and learning process has shifted to online learning. It quite challenges the teachers as well as the students to fully support the success of the online classes.Teachers are required to be more creative in delivering the learning materials that will be given to their students. Meanwhile, students are encouraged to be autonomous learners. This paper aims to investigate the students’ perceptions toward the implementation of the ZOOM application to support the online learning process and explore how this application gives a new shape in the educational industry. The qualitative approach was chosen for this study. The data were obtained from questionnaires and interviews. Based on the findings, there are some perceptions about the implementation of ZOOM to support online learning. The result showed that most students thought implementation of e-learning should be improved continuously. Surprisingly, it gave significant changes toward the learning and teaching process, especially during covid-19 itself.